2021
DOI: 10.1007/s12035-020-02243-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosome Release Is Modulated by the Mitochondrial-Lysosomal Crosstalk in Parkinson’s Disease Stress Conditions

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive loss of dopaminergic neurons in the substantia nigra (SN) pars compacta region of the brain. The main pathological hallmark involves cytoplasmic inclusions of αsynuclein and mitochondrial dysfunction, which is observed in other part of the central nervous system other than SN suggesting the spread of pathogenesis to bystander neurons. The inter-neuronal communication through exosomes may play an important role in the spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…The qRT-PCR validation for the DEmRNA of interest and related DElncRNAs revealed upregulated expression level of NDUFB7 in pre-rehab PWPs compared to post-rehab PWPs. The release of damage-related molecules of mitochondria is a potential mechanism connecting mitochondrial dysfunction with systemic inflammation in the setting of various diseases, such as PD (Currim et al, 2021 ). A previous study indicated that mildly damaged mitochondria were primed by serine/threonine-protein kinase PINK1 and Parkin and generated mitochondrial-derived vesicles (MDVs; Mclelland et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The qRT-PCR validation for the DEmRNA of interest and related DElncRNAs revealed upregulated expression level of NDUFB7 in pre-rehab PWPs compared to post-rehab PWPs. The release of damage-related molecules of mitochondria is a potential mechanism connecting mitochondrial dysfunction with systemic inflammation in the setting of various diseases, such as PD (Currim et al, 2021 ). A previous study indicated that mildly damaged mitochondria were primed by serine/threonine-protein kinase PINK1 and Parkin and generated mitochondrial-derived vesicles (MDVs; Mclelland et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an inhibitor of mammalian target of rapamycin, rapamycin has been reported to inhibit exosome release from neuronal cells and glial cells. 65 Moreover, mammalian target of rapamycin reportedly regulates the lysosomeeMVB interaction and exosome release in smooth muscle cells. 23 The results with rapamycin confirmed the vital role of lysosomes in the regulation of exosome release in podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Several diseases can arise due to lysosomal dysfunction, as exemplified by the neurodegenerative disorder [ 180 ]. In other diseases, such as AD and Parkinson’s, toxic proteins are aggregated inside EVs that once released, contribute to inflammation and disease progression [ 181 , 182 , 183 ]. Presence of key proteins, such as DJ-1, Parkin or PINK1 are all involved in lysosomal dysfunction, mitophagy, and neurodegenerative diseases [ 184 , 185 ].…”
Section: Lysosomes and Evsmentioning
confidence: 99%